(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
Interaction of well-known DNA minor groove binder Hoechst 33258 and Calf Thymus DNA without and in the presence of increasing amount of dimethyl sulfoxide (DMSO) was studied using UV-vis spectroscopy methods. Thermal melting results show that the melting temperature of Hoechst–DNA complex decreases while increasing of DMSO content. It was shown that DNA is more stable at low DMSO content (5% v/v) rather, than at high concentrations (10–20%).